2019
DOI: 10.1039/c9ra08038d
|View full text |Cite
|
Sign up to set email alerts
|

Direct biodiesel production from wet spent coffee grounds

Abstract: Utilization of waste spent coffee grounds (SCG) remains limited and requires pre-treatment before being discarded to avoid pollution to the environment. Lipids contained in SCG could be converted to biodiesel through an in situ transesterification method. Current in situ transesterification of wet SCG biomass, conducted at high reaction temperature to reduce the water effect and reduce reaction time, is energy intensive. A new approach, which combines simultaneous extraction-transesterification in a single ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…These results suggest that the addition of MTBE unexpectedly compromised the esterification of the AG within sorghum DDGS. While this solvent combination was successful for previously cited research (Sakthivel et al, 2013; Tarigan et al, 2019), the MTBE may be interfering with some components of our reaction mixture that affects esterification to the extent that larger quantities of methanol (RC 17–20) are required to overcome its effect. RC 17 and 18 gave good yields; however, there is no benefit to adding MTBE as a co‐solvent in the IST reaction of milo DDGS to FAME.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…These results suggest that the addition of MTBE unexpectedly compromised the esterification of the AG within sorghum DDGS. While this solvent combination was successful for previously cited research (Sakthivel et al, 2013; Tarigan et al, 2019), the MTBE may be interfering with some components of our reaction mixture that affects esterification to the extent that larger quantities of methanol (RC 17–20) are required to overcome its effect. RC 17 and 18 gave good yields; however, there is no benefit to adding MTBE as a co‐solvent in the IST reaction of milo DDGS to FAME.…”
Section: Resultsmentioning
confidence: 80%
“…Studies have shown that using a co‐solvent can improve the conversion of AG to FAME by removing the mass transfer resistance created at the interface of the oil and alcohol, resulting in greater miscibility at the interface and higher reaction rates. Examples cited in the literature include improving the IST conversion of the AG in spent coffee grounds to FAME from 77% to 89% (Tarigan et al, 2019) and up to a 20% increase for the conversion of Jatropha curcas oil to FAME (Sakthivel et al, 2013). To improve upon the 79.8% yield achieved in RC 8 (Table 3), methyl tert‐butyl ester (MTBE) was employed as a co‐solvent (Table 4, RC 15–20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional extraction soxhlet method was used to determine the quantity of palm kernel oil and the result was compared with the AEE. The procedure we followed for the soxhlet extraction has been reported elsewhere (Al-Hamamre et al 2012;Tarigan et al 2019). About 20 g of grounded palm kernel was extracted in the soxhlet apparatus using hexane as an extracting agent under reflux condition for 30 minutes.…”
Section: Oil Extraction Using Soxhlet Methodsmentioning
confidence: 99%